Exploring general and sports nutrition and food knowledge in elite male Australian athletes - Devlin, B. L.; Belski, R. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
Nutrition knowledge is believed to influence nutritional intake, which in turn influences performance in elite athletes. There is currently no published data on the nutrition knowledge of elite Australian Football (AF) players. The purpose of this study was to gain insight into the current level of general and sports nutrition knowledge in elite male AF athletes. Forty six elite male AF players (23.5 ± 2.8 years) answered 123 questions relating to five areas of nutrition knowledge: dietary recommendations, sources of nutrients, choosing everyday foods, alcohol and sports nutrition. Demographic details and perceptions of nutrition knowledge were collected for all participants. The mean nutrition knowledge score was 74.4 ± 10.9 (60.5%). The highest score was obtained in sports nutrition section (17.9 ± 3.0, 61.7%). The dietitian was selected as the first source of information by 98% of athletes, with club trainer and teammates as second choice for 45.7% and 23.9% of athletes, respectively. The majority of athletes correctly answered questions regarding recommendations to increase fruit and vegetable intake and decrease fat intake (95.6%, 91.1% and 93.3% correct respectively). While 80% of the athletes were aware fat intake should predominately be made up of unsaturated fat, they were less able to identify food sources of unsaturated fats (35.6% and 24.4% correct for statements regarding monounsaturated and polyunsaturated fats, respectively). Broad nutrition messages and recommendations appear to be well understood; however, gaps in nutrition knowledge are evident. A better understanding of nutrition knowledge in athletes will allow nutrition education interventions to target areas in need of improvement.